P23 Evaluation of exposure to vancomycin in neonates with current dosing approaches. Issue 6 (17th May 2019) - Dao, K; Guidi, M; Andre, P; Giannoni, E; Fuchs, A; Pfister, M; Buclin, T; Csajka, C
Abstract : Background: Several neonatal dosing recommendations for vancomycin are found in the literature, variably based on age, renal function and body weight. Still there is no consensus regarding optimal initial dosing in term or preterm neonates. Our objective was to evaluate and compare how current dosing approaches perform with respect to target plasma concentration attainment, using a comprehensive population PK model of vancomycin developed in a large cohort of neonates. Methods: A single-compartment, linear elimination population pharmacokinetic model incorporating postmenstrual age, kidney function and body weight as covariates was elaborated using NONMEM®, based on 1848 vancomycin concentration values measured in 405 neonates during routine TDM. The model was then used to simulate the distribution of vancomycin concentrations resulting from 20 dosing guidelines identified in the literature. Proportions of patients within and above target exposure were used as a performance measure of each dosing regimen, defining target as AUC24 /MIC ratio of 400–700 h and trough concentration of 10–20 mg/L, both on days 1 and 7 of treatment. Results: Only 2 out of 20 current dosing recommendations (Neonatal Formulary 7 and Neofax® meningitis regimens) ensured target attainment in about 60% of neonates on both days 1 and 7. Most other guidelines produced below-target exposure in a large fraction of patients (22–97%), except two that frequently produced overexposure (55–66%). Conclusion: A majority of currently used vancomycin dosing regimens proposed in the literature failed to ensure target attainment in at least 60% of neonates. It is important that concentration exposure associated with best chances of therapeutic success is promptly reached, in particular in neonatal units having a high prevalence of coagulase negative Staphylococci. We recommend electing an effective dosage regimen, with a loading dose, to ensure early target attainment in a majority of patients. Subsequent therapeutic concentration monitoring remains warranted to further individualize vancomycin dosage and optimize exposure in all patients. Disclosure(s): Nothing to disclose